Ethics and science: between logical positivism and Islamic education - A comparative study - - Allihyani, Smyah Ghazi (Journal of Educational and Psychological Sciences, 2020)
The research aims to study and analyze the perception of the logical positivism of ethics and science, and study and analyze the perception of Islamic education for ethics and science, in addition to monitoring similarities and differences between the perception of logical positivism and Islamic education for ethics and science, and finally draw the most important conclusions from the comparison between the logical positivism perception and Islamic education of ethics and science.Research Methodology: George Bereday Curriculum's four-step comparative approach: description – interpretation – juxtaposition – comparison.The research reached several results, the most prominent of which are:1- Islamic education was distinguished from logical positivism in its belief that benign morals are a fixed source; it derives from Islamic sources the Noble Qur’an and pure Sunnah, at a time when morals are considered relative as perceived by logical positivism.2- Islamic education was distinguished in its view of Islamic morals as absolute and does not change with the change of time or place, at a time when the logical positivism considered ethics as separate from social life and its criterion of human needs, will and choice.3- Islamic education was distinguished from the logical positivism in its conception of science where its view was more general and more comprehensive in the source of knowledge, for God Almighty is the source of knowledge and to him all things are returned, then nature and its facts and laws that come from the arrangement of God Almighty and the Creator and its use of human beings come.4- Islamic education was distinguished from the logical positivism in its belief in the unseen and the testimony, so the mind and the senses are all tools by which the believer inferred the net belief on the existence of a creator and mastermind of this great universe. The great.5- Islamic education was distinguished by the comprehensiveness of its view of the mind, because it is based on sincere faith and common sense, on which sound thinking is based.6- Islamic education was more comprehensive than the logical positivism in the steps of the scientific method (research) in studying natural phenomena and various fields of knowledge, due to its dependence mainly on the divine (revelation) source which is from God Almighty being the source of knowledge and knowledge.
Keywords: phenomenological; empirical; post- ethics; meta- ethics; ethics